'I am drug dependent': a study of self-identification and prior criminal justice contact using archival data from the Drug Use Monitoring in Australia (DUMA) program. Issue 1 (2nd January 2022) - Langfield, Cameron T.; Payne, Jason L.
ABSTRACT: Identity theories have long influenced criminological thinking, and much of that work warns of deviant certification and negative appraisals as promoting criminal continuity. In the drug-use literature, similar themes have emerged linking drug-use continuity to the strength of one's identity as 'dependent' or 'addicted' to drugs. Using archival data drawn from the Drug Use Monitoring in Australia (DUMA) program, we explore the correlation between criminal justice contact and the self-identification of a drug dependency among a sample of recent drug-using police detainees. We find, holding constant a detainee's frequency, longevity and type of drug use, that contact with the criminal justice system is statistically associated with higher odds of self-identifying as dependent. Further, we found those detainees who have more frequent criminal justice contact more likely to report themselves as dependent. This finding contributes to ongoing research into the complexity of identity and the management and engagement of drug-using offenders in treatment programs offered throughout the criminal justice system.